A case report of benzodiazepine withdrawal delirium due to accidental discontinuation of benzodiazepines in cancer perioperative period - Junji Yamaguchi; Ryoichi Sadahiro; Saho Wada; Eri Nishikawa; Tatsuto Terada; Rika Nakahara; Hiromichi Matsuoka (PCN Reports)
Abstract Background Benzodiazepines are known for their possible risk of delirium, especially when administered to older adults or during the perioperative period. However, the risk of sudden discontinuation of benzodiazepines and subsequent withdrawal delirium seems to be underappreciated and not properly recognized in cancer treatment, even among healthcare workers. Case Presentation A man in his late 70s was diagnosed with rectal cancer and had a history of taking etizolam and alprazolam for over 15 years. After hospitalization for cancer, these benzodiazepines were discontinued abruptly 2 days before the surgery, due to concerns about benzodiazepine‐related delirium. After half a day, severe benzodiazepine withdrawal symptoms, such as disorientation, agitation, tachycardia, diaphoresis, and muscle twitching, appeared. The patient was diagnosed with delirium associated with benzodiazepine withdrawal, and his symptoms subsided soon after re‐administration of benzodiazepines. Despite development of mild postoperative delirium, the operation was performed safely. Conclusion The rapid and abrupt discontinuation of benzodiazepines before cancer surgery could impose a high risk of benzodiazepine withdrawal delirium in patients, which makes the management of psychiatric symptoms in the perioperative period more complex and difficult. We believe that it is necessary to highlight the risks of withdrawal delirium and abrupt benzodiazepine discontinuation in cancer treatment. Moreover, re‐education on this topic is essential for healthcare workers.